Ionic Liquid Lubricant for Ultra-Low Head-Media Spacing in Hard Disk Drives - Kouki Hatsuda (Japanese Society of Tribologists, 2020)
In order to attain high recording density in a hard disk drive, reduction of the head-media spacing (HMS) is crucial. The contribution of lubricant thickness to the HMS is a significant factor in performance. Because the lubricant thickness is on the order of angstroms, molecules of long-chain lubricants, such as perfluoroether, must lay parallel to the magnetic disk surface to reduce lubricant thickness. In this study, new lubricants were designed using ionic liquids (ILs). The ILs had smaller molecular weight than that of current perfluoropolyether (PFPE) lubricants but with lower evaporation loss. The molecular conformation of the ILs was controlled by two hydroxyl groups, which were placed in a cation moiety at both terminal ends (IL-1) or placed on one side of the cation (IL-2). The monolayer thickness of IL-1 and IL-2 was seen to be 0.6 nm and 1.2 nm, respectively. The adhesion force at a lubricant thickness of 1.0 nm decreased in the order: PFPE (Z-Dol 2000) > IL-2 > IL-1. The small adhesion force, which is one of the essential parameters for low flight of a magnetic head, was achieved by changing the molecular conformation of the IL.